2015
DOI: 10.1051/ijmqe/2015013
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the guardbanding to ensure acceptable risk decision in the declaration of conformity

Abstract: Abstract. This article proposes a mathematical procedure designed to generate an economical measurement model for determining the risk of decision error (customer risk). The model includes the guardbanding to reduce the impacts of measurement errors. A mathematical model is provided as an example, and conclusions are drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The linear approximation of an actual marginal manufacturing cost under the reference condition, as shown in figure 5, is a possible interpretation of expression (20). Although it may be a difficult task to obtain the actual marginal manufacturing cost, the relationships given by expressions ( 38 In other words, the specific form of g(W) is not required for the purpose of this study.…”
Section: Possible Interpretation Of the Proposed Manufacturing Costmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear approximation of an actual marginal manufacturing cost under the reference condition, as shown in figure 5, is a possible interpretation of expression (20). Although it may be a difficult task to obtain the actual marginal manufacturing cost, the relationships given by expressions ( 38 In other words, the specific form of g(W) is not required for the purpose of this study.…”
Section: Possible Interpretation Of the Proposed Manufacturing Costmentioning
confidence: 99%
“…Forbes [17] not only suggested a way to determine acceptance interval based on the Bayesian decision-making approach but also showed the influence of unknown systematic effects associated with the measurement system. Other interesting studies [18][19][20][21][22] were introduced in Pendrill's reviews or reported recently. Some of the above studies were incorporated in JCGM 106.…”
Section: Introductionmentioning
confidence: 99%